PENGARUH PERTUMBUHAN EKONOMI, PAD, DAU TERHADAP PENGALOKASIAN ANGGARAN BELANJA MODAL PADA KABUPATEN/KOTA SUMATERA SELATAN - Putri Retno Aryani; Kurnia Krisna Hari (Jurnal Akuntansi dan Keuangan (JAK), 2019)
This research is aimed at determining the influence ofeconomic growth, local revenue and general fund allocation toward appropriation of capital budget In Districts/City in South Sumatera Province. The samples used in this study were 11 districts/cities in South Sumatera Province in line with the source of Realization Report Budget (APBD) which was accessed from www.djpk.depkeu.go.id and Economic Growth which was obtained from the Central Statistics Agency of South Sumatera Province. The data used in this research was secondary data. The technique of analyzing the data was using multiple regression test. Simulataneously, the results showed that Economic Growth, Local Revenue and General Fund Allocation had positive significant influence toward capital expenditures. While, partially, the results showed that Economic Growth had no positive significant influence toward toward Capital Expenditure, regional revenue had no positive significant influence toward Capital Expenditure, General Fund Allocation had positive significant toward Capital Expenditure.